HOW DOES GREEN FACTOR AFFECT SATISFACTION AND PURCHASE INTENTION ON ECO-FRIENDLY PRODUCTS? - Celline, Aprilia; Keni , Keni (Graduate Program of Universitas Tarumanagara, 2024)
The high population in Indonesia causes significant accumulation of waste, leading to waste management problems and landfills adjacent to the community. This unrest created criticism of the government, prompting the issuance of plastic waste reduction regulations. The government hopes that the public can make an active contribution in overcoming this problem. Correspondingly, people are turning to eco-friendly products, including skin care products from companies like Innisfree. This study explores the influence of green value perception and green attitudes on green satisfaction and green purchase intent on the product, using Partial Least Square-Structural Equation Modelling (PLS-SEM) analysis to test the hypothesis. This study aims to empirically examine the influence of green value perception and green attitude towards green purchase intention with green satisfaction as mediation. This study used a descriptive research design with cross-sectional data collection techniques and used non-probability sampling techniques with convenience techniques on 213 environmentally friendly skin care users. The questionnaire is distributed through an online Google Form. This research shows that green attitudes and green satisfaction have a positive and significant influence on green purchase intentions in customers of environmentally friendly skin care products, but the perception of green value does not have a positive and significant influence on green purchase intentions. Furthermore, green value perceptions and green attitudes have a positive and significant effect on green satisfaction. Furthermore, green satisfaction can mediate positively and significantly green value perceptions and green attitudes towards green purchase intent. Lastly, green satisfaction can mediate positively and significantly green attitudes and green attitudes towards green purchase intentions.